MoO3-rGO nanocomposites for electrochemical energy storage - Khandare, Lina; Late, Dattatray J. (Applied Surface Science, 2017)
We have synthesized the one dimensional (1D) MoO3 nanorods and MoO3-rGO nanocomposite by using sonochemical dispersion method at low temperature. The obtained products were characterized by using Raman spectroscopy, FT-IR, SEM, TEM and HR-TEM. We have demonstrated the electrochemical properties of MoO3 nanorods and MoO3-rGO nanocomposites. The specific capacitance for MoO3 nanorods and MoO3-rGO nanocomposite was calculated to be 3.3 F/g and 22.83 F/g at current density of 0.3 A/g respectively. The nanocomposite of MoO3-rGO shows the better electrochemical performance as compared to pristine MoO3 nanorods sample due to improvement in the conductivity. Our result suggests that the MoO3-rGO nanocomposites material has great potential for electrochemical energy storage and related applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Nanocomposites; Nanorods; Storage (materials); Temperature

Growth of Mo-doped Ni3S2 nanorods array for superior overall water splitting reaction - Sharma, Pooja; Khandare, Lina; Saha, Arindam; Chaure, Nandu B.; Yengantiwar, Ashish (International Journal of Hydrogen Energy, 2025)
Designing novel, efficient and cost-effective dual-functional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using an alkaline electrolyte is crucial for establishing a sustainable hydrogen economy and transitioning to a society powered by renewable energy sources. In the present work, Mo-doped nickel sulfide (Mo-Ni3S2) nanorods were grown on Ni-treated nickel foam (N-NF) substrate via a two-steps hydrothermal method. Specifically, Mo-Ni3S2/N-NF surface consists of nanorods-like morphology, which provides extensive area for percolation of electrolyte, that resulting in outstanding catalytic performance. Such a well-synthesized electrode exhibited superior performance and stability for OER as compared with pristine Ni3S2/NF and bare nickel foam (NF) electrodes. In addition, Mo-Ni3S2/N-NF electrode provides good HER activity and confirms its dual-functionality in alkaline medium. Our champion Mo-Ni3S2/N-NF electrocatalyst delivers best OER overpotential of 230 mV at current density of 100 mA/cm(2). Also, it provides HER overpotential of 100.6 mV at a current density of 10 mA/cm(2). Both OER and HER are carried out in the presence of 1 M KOH alkaline electrolyte. OER stability of the best-performed Mo-Ni3S2/N-NF electrode demonstrates almost constant current density similar to 120 mA/cm(2), which retains 90% of original value after continuously tested for the duration of 22 h. The total cell voltage of 1.56 V is provided by Mo-Ni3S2/N-NF integrated system and it demonstrates a good stability for duration of 22 h. Our approach provides a new insight into developing earth-abundant, inexpensive and superior dual-functional electrocatalyst for overall water splitting reaction (WSR).
Keywords: Dual-functional electrocatalyst; HER; Mo doping; Nickel sulfide nanorods; OER; overall water splitting